Inspecting the True Identity of Herbal Materials from Cynanchum Using ITS2 Barcode - Guo, Mengyue; Ren, Li; Pang, Xiaohui (Frontiers in Plant Science, 2017)
Cynanchum is a large genus with some important medicinal species in China. The medicinal species in Cynanchum are easily confused, leading to potential safety risks. In this study, the internal transcribed spacer 2 (ITS2) barcode was used to discriminate the medicinal plants in Cynanchum. The identifying capability of ITS2 was assessed using the specific genetic divergence, BLAST1, neighbor-joining (NJ) tree, maximum-likelihood (ML) tree, and single-nucleotide polymorphism (SNP) methods. Results indicated that the intra-specific genetic divergences of Cynanchum species were lower than their inter-specific genetic divergences. Of the 87 samples from 17 species, ITS2 showed a high identification efficiency of 90.8% and 87.4% at the species level through BLAST1 and the nearest distance methods. NJ tree and ML tree also demonstrated the suitability of ITS2 to differentiate Cynanchum species. Meanwhile, a stable SNP was found, and it could accurately authenticate C. paniculatum and C. atratum. Furthermore, we collected 64 commercial samples from three commonly used herbal medicines and evaluated the capability of ITS2 to survey their authentication. Of these samples, Cynanchi Atrati Radix et Rhizoma (Baiwei) showed a potential safety problem, and all the 11 test samples were adulterants. In conclusion, ITS2 can distinguish medicinal species in Cynanchum effectively, and its application could greatly improve the identification efficiency and accuracy of commercial herbal medicines in this genus.